2015
DOI: 10.1111/1471-0528.13788
|View full text |Cite
|
Sign up to set email alerts
|

Risk of postnatal depression or suicide after in vitro fertilisation treatment: a nationwide case–control study

Abstract: Results: Initial analyses showed that PND was more common in the control group than the IVF group (0.8% vs. 0.4%; p=0.04). However, these differences disappeared when confounding factors were controlled for. A history of any psychiatric illness (p=.000; OR=25.5; 95 % CI=11.7-55.5), any previous affective disorder (p=,000; OR=26.0; 95%CI=10.5-64.0) or specifically a personality disorder (p=.028; OR=3.8; 95 % CI=1.2-12.7) increased the risk of PND. No woman in either group committed suicide during the first year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Registry studies including large populations also have failed to show an association between fertility treatments and postpartum depression (25,26). However, they may be limited by a cross-sectional design, the inability to differentiate between different kinds of fertility treatments (25), or the need to rely retrospectively on registered treatments and coded diagnoses of depression (26).…”
mentioning
confidence: 99%
“…Registry studies including large populations also have failed to show an association between fertility treatments and postpartum depression (25,26). However, they may be limited by a cross-sectional design, the inability to differentiate between different kinds of fertility treatments (25), or the need to rely retrospectively on registered treatments and coded diagnoses of depression (26).…”
mentioning
confidence: 99%
“…Another study investigated the association between suicidal ideation and In Vitro Fertilization (IVF). It was hypothesised that women conceiving with IVF potentially have a higher risk of postnatal depression and suicide however, it was demonstrated that IVF does not increase rates of postnatal depression and suicide (Vikstrom et al, 2017).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…However, an Italian study showed slightly higher anxiety and/or depression rates in both women and partners awaiting IVF/ICSI with respect to the general population, while 18.5% of women and 7.4% of partners who had scored under the threshold at the beginning of the procedures scored above-threshold on anxiety or depression rating scales at the end of the procedures [15]. However, most studies did not find differences in depression between infertile women undergoing treatment for infertility and controls [16][17][18][19][20][21], and one found its prevalence to be reduced in IVF women compared to controls [22]. Results match the conclusions of systematic reviews and meta-analyses, which ruled out a relationship between MAR and postpartum depression [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Women score higher than their partners on anxiety and depression [15,17]; a longer infertility history and having an anxious partner appeared to increase anxiety and depression in IVF women [15]. The main risk factors for the development of perinatal depression in women undergoing MAR were past major depressive episodes [28] or other psychiatric disorders [18,20], and past unsuccessful infertility treatment cycles, which also increase the odds for anxiety symptoms [16,29].…”
Section: Introductionmentioning
confidence: 99%